Polyether complexes of groups 13 and 14. (11th April 2016) - Swidan, Ala'aeddeen; Macdonald, Charles L. B.
Abstract : Notable aspects of the chemistry of polyether complexes of group 13 and 14 elements are reviewed. Abstract : Notable aspects of the chemistry of complexes of polyether ligands including crown ethers, cryptands, glycols, glymes, and related polyether ligands with heavier group 13 and 14 elements are reviewed with a focus on results from 2005 to the present. The majority of reported polyether complexes contain lead(ii ) and thallium(i ) but recent breakthroughs in regard to the preparation of low oxidation state reagents of the lighter congeners have allowed for the generation of complexes containing indium(i ), gallium(i ), germanium(ii ), and even silicon(ii ). The important roles of ligand size, donor types, and counter anions in regard to the chemical properties of the polyether complexes is highlighted. A particular focus on the structural aspects of the numerous coordination complexes provides a rationale for some of the spectacular contributions that such compounds have made to Modern Main Group Chemistry .